2017
DOI: 10.1038/s41598-017-04896-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of calorie restriction on mouse skeletal muscle is sex, strain and time-dependent

Abstract: Loss of skeletal muscle mass and function occurs with increasing age. Calorie restriction (CR) increases the lifespan of C57Bl/6 mice, but not in the shorter-lived DBA/2 strain. There is some evidence that calorie restriction reduces or delays many of the age-related defects that occur in rodent skeletal muscle. We therefore investigated the effect of short (2.5 month) and longer term (8.5 and 18.5 months) CR on skeletal muscle in male and female C57Bl/6 and DBA/2 mice. We found that short-term CR increased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 78 publications
3
36
0
Order By: Relevance
“…Because the inhibition of myostatin increases muscle mass in mice (42), any influence on the ability of AgRP neurons to regulate myostatin may affect the preservation or restoration of lean mass; we suggest that the deletion of Crat in AgRP neurons represents one such influence over AgRP neurons. This finding might have implications for muscle degenerative diseases such as cachexia or muscle dystrophy, but further research is needed, as CR has differential effects on muscles dependent on strain, sex, and time (43). Recent studies also suggest osteocytes act as a body weight sensor, regulating food intake independent of leptin to maintain body weight (44).…”
Section: Discussionmentioning
confidence: 98%
“…Because the inhibition of myostatin increases muscle mass in mice (42), any influence on the ability of AgRP neurons to regulate myostatin may affect the preservation or restoration of lean mass; we suggest that the deletion of Crat in AgRP neurons represents one such influence over AgRP neurons. This finding might have implications for muscle degenerative diseases such as cachexia or muscle dystrophy, but further research is needed, as CR has differential effects on muscles dependent on strain, sex, and time (43). Recent studies also suggest osteocytes act as a body weight sensor, regulating food intake independent of leptin to maintain body weight (44).…”
Section: Discussionmentioning
confidence: 98%
“…Studies on skeletal muscle showed that short-term DR (3 months) improved MuSC function in culture and during muscle regeneration in vivo [76]. By contrast, DR had negative effects on the colonyforming capacity of MuSCs and muscle fiber size after muscle regeneration [77]. Experiments on the hematopoietic system from our group revealed that longterm DR delays early aging of HSCs when applied to 3-12 month old mice by slowing IGF-dependent HSC proliferation, thus impairing aging-associated increases in HSC numbers and concomittant decreases in the repopulation capacity compared with ad libitum (AL)-fed mice [78].…”
Section: Dietary Restriction (Dr) and Stem Cell Functionmentioning
confidence: 99%
“…S1, after 2-week acclimation period, mice were divided into two weight-matched groups and fed with different diets, including ad libitum diet (AL, n=40) and caloric restriction diet (CR, n=40) for a period of 4 weeks, respectively. CR was progressive, initiated at 10% restriction during the rst week, 25% during the second week, and to 40% for the remainder experimental period, according to the method described previously [49,69,70]. The components of AL diet and CR diet are shown in Table S1.…”
Section: Animal Modelsmentioning
confidence: 99%